2003
DOI: 10.1124/dmd.31.6.742
|View full text |Cite
|
Sign up to set email alerts
|

INVOLVEMENT OF CYP3A4, CYP2C8, AND CYP2D6 IN THE METABOLISM OF (R)- AND (S)-METHADONE IN VITRO

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:To clarify the oxidative metabolism of methadone (R)-and (S)-enantiomers, the depletion of parent (R)-and (S)-methadone and the formation of racemic 2-ethylidene-1,5-dimethyl-3,3-diphenylpyrolidine were studied using human liver microsomes and recombinant cytochrome P450 enzymes. Based on studies with isoform-selective chemical inhibitors and expressed enzymes, CYP3A4 was the predominant enzyme involved in the metabolism of (R)-methadone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
132
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(140 citation statements)
references
References 29 publications
8
132
0
Order By: Relevance
“…In our previous study in 52 Malay male subjects given a single 8 mg dose of methadone, we found a wide variability in its clearance, consistent with other studies previously reported [28]. The variability in our 52 subjects could not be explained by polymorphisms at the CYP2D6 locus, a very polymorphic gene in our population [19][20][21], another enzyme implicated in methadone metabolism [29]. This led us to investigate the genetic polymorphism at the CYP3A4 locus among heroin drug users.…”
Section: Discussionsupporting
confidence: 70%
“…In our previous study in 52 Malay male subjects given a single 8 mg dose of methadone, we found a wide variability in its clearance, consistent with other studies previously reported [28]. The variability in our 52 subjects could not be explained by polymorphisms at the CYP2D6 locus, a very polymorphic gene in our population [19][20][21], another enzyme implicated in methadone metabolism [29]. This led us to investigate the genetic polymorphism at the CYP3A4 locus among heroin drug users.…”
Section: Discussionsupporting
confidence: 70%
“…Some controversy exists in the literature regarding which cytochrome P450 (P450) isoform(s) plays the primary role in hepatic metabolism and clearance of MD. In previous studies, the predominant mediator of MD metabolism was thought to be CYP3A4, and numerous in vitro and in vivo studies have shown CYP3A4 involvement in the metabolism of MD in human liver or intestines (Wang and DeVane, 2003;Gerber et al, 2004;Kharasch et al, 2004). However, recent studies suggest that CYP2B6 is also involved in the metabolism of MD and may possess a higher affinity for MD metabolism compared with that of CYP3A4 (Gerber et al, 2004;Kharasch et al, 2008;Weschules et al, 2008).…”
mentioning
confidence: 99%
“…Kharasch and colleagues recently demonstrated that CYP2B6 is of greater importance in the metabolism of methadone than CYP3A4 (17). Methadone undergoes oxidative metabolism to inactive metabolites by several other cytochrome P450 variants, including CYP2C19, CYP2D6, and CYP2C8 (11)(12)(13)(14)(15)(16)(17). COBI is not an inhibitor of CYP2B6; however, it is a moderate inhibitor of CYP2D6 (22).…”
Section: Discussionmentioning
confidence: 99%
“…Methadone is administered as a racemic of R and S enantiomers, with the R enantiomer having the greater potency at the mu-opioid receptor (10). Methadone undergoes oxidative metabolism to inactive metabolites by several cytochromes, including cytochrome P450 2B6 (CYP2B6), CYP3A4, CYP2C19, CYP2D6, and CYP2C8 (11)(12)(13)(14)(15)(16)(17). Substantial interindividual variation exists (18,19); therefore, changes in methadone plasma concentrations do not necessarily predict the pharmacodynamic response.…”
mentioning
confidence: 99%